ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN BERBASIS GAME WORDWALL MATERI PENJUMLAHAN DAN PENGURANGAN MATEMATIKA SISWA KELAS II SEKOLAH DASAR - Syahputri, Dinda Dwi; Mansur, Nabilah; Kamil, Nurdin; Nurani, Dwi Cahaya; Astika, Ruri Tria; Najwa, Wulida Arina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low comprehension of second-grade elementary school students regarding addition and subtraction operations due to the use of conventional and less interactive learning media. This condition causes some students to experience difficulty understanding basic mathematical concepts, leading to learning outcomes that have not yet reached the standard of completeness. This study aims to analyze the needs for Wordwall game-based learning media on addition and subtraction material and to identify the potential for its implementation in increasing students' interest and comprehension. The method used is descriptive qualitative, involving teachers and students through observation, interviews, and documentation. Data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results show that teachers still predominantly use traditional media even though technology facilities are supportive, while students demonstrate high enthusiasm for visual media and interactive learning activities. Some students still memorize without fully grasping the concepts, highlighting the need for media that provides engaging, repetitive practice. The needs analysis indicates that Wordwall has great potential as a learning medium capable of increasing students' motivation, engagement, and understanding of basic arithmetic operations, making it relevant for implementation in second-grade Mathematics learning.